Continuous and multidimensional assessment of resilience based on functionality analysis for interconnected systems. Issue 4 (3rd April 2019) - Kamissoko, Daouda; Nastov, Blazo; Benaben, Frederick; Chapurlat, Vincent; Bony-Dandrieux, Aurelia; Tixier, Jérôme; Amendeep, Amendeep; Daclin, Nicolas
Abstract: The increasing number of disruptions to critical infrastructure, like natural disasters, terrorist attacks or internal failure is today a major problem of society. Concern is even greater when considering the interconnected nature of critical infrastructure, which might lead to failure propagation, causing domino and cascade effects. To mitigate such outcomes, critical infrastructure must recover its capacity to function with regard to several criteria. Stakeholders must therefore analyse and improve the resilience of critical infrastructure before any disruption occurs, and base this analysis on different models so as to guarantee society's vital needs. Current resilience assessment methods are mainly oriented toward the context of a single system, thus narrowing their criteria metrics, limiting flexibility and adaptation to other contexts and overlooking the interconnected nature of systems. This article introduces a new tool-equipped approach that makes it possible to define a model to evaluate the functionalities of interconnected systems. The model is then used to assess the resilience of these systems based on simple and generic criteria that can be extended and adapted. Several assertions related to the concept of resilience and some resilience indicators are also introduced. A case study provides the validation performed by experts from several domains.